Chest radiograph abnormalities in patients hospitalized with leptospirosis in the city of Salvador, Bahia, Brazil - Matos,Eliana Dias (2001)
This study was designed to estimate the prevalence of pulmonary radiograph abnormalities and describe the distribution of the patterns of radiographic alterations among patients hospitalized with leptospirosis. Chest radiographs of 139 patients hospitalized with leptospirosis in Couto Maia Hospital, in Salvador, Bahia, Brazil, between July, 1997, and July, 1999, were analyzed. The radiographs were requested soon after hospital admission, independent of the clinical manifestations of the patients. Only the first radiograph was considered. Pulmonary radiograph alterations were recorded in 35/139 patients (25.2%); 95% mid-point confidence interval = 18.5% to 32.9%. Among the patients with radiograph alterations, alveolar infiltrate was seen in 26/35 (74.3%). The lesions were bilateral in 54.3% and located in the inferior lobes in 45.5%. Pleural effusion, represented by blunting of the costo-phrenic angle, was detected in 8.6% of the patients. The pattern of the pulmonary alterations, predominantly bilateral alveolar infiltrates, is consistent with the evidence that the basic pulmonary alteration in leptospirosis is a generalized capillaritis.